2017
DOI: 10.1038/s41598-017-04474-2
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid and 5-HEPE enhance macrophage-mediated Treg induction in mice

Abstract: Eicosapentaenoic acid (EPA) is an omega-3 fatty acid with immunomodulatory and anti-inflammatory effects. Beyond its direct effects, the metabolic products of EPA also regulate various immune responses. Animal experiments demonstrated that EPA reduces adipose inflammation in high fat diet-induced obese mouse. However, the effects of EPA on infiltrated immune cell populations in adipose tissue and underlying mechanisms remain to be elucidated. We performed flow cytometry of stromal vascular fraction of epididym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Surprisingly, C57BL/6 and ob/ob mice fed with 5% Eicosapentaenoic acid mixed into chow diet had an increase in the number of Treg cells in epididymal adipose tissues compared with control mice fed with normal chow. However, only C57BL/6 mice showed lowered body and adipose tissue weight than controls ( 87 ). Recently, it was reported that oral administration of thiazolidinediones (TZDs), PPARγ agonists with insulin-sensitizing function, in HFD-fed mice enhanced the fraction and number of Treg cells specifically in epididymal adipose tissue ( 11 , 27 ).…”
Section: The Therapeutic Potential Of Adipose-resident Treg Cells Inmentioning
confidence: 99%
“…Surprisingly, C57BL/6 and ob/ob mice fed with 5% Eicosapentaenoic acid mixed into chow diet had an increase in the number of Treg cells in epididymal adipose tissues compared with control mice fed with normal chow. However, only C57BL/6 mice showed lowered body and adipose tissue weight than controls ( 87 ). Recently, it was reported that oral administration of thiazolidinediones (TZDs), PPARγ agonists with insulin-sensitizing function, in HFD-fed mice enhanced the fraction and number of Treg cells specifically in epididymal adipose tissue ( 11 , 27 ).…”
Section: The Therapeutic Potential Of Adipose-resident Treg Cells Inmentioning
confidence: 99%
“…In contrast to AA, EPA and DHA were rarely detectable in the clinical mastitic milk, while the concentrations of metabolites of the n‐3 PUFAs, such as 5‐HEPE and 18‐HEPE were increased. EPA and DHA are the essential fatty acid for mammalians and their metabolites are reported to have anti‐inflammatory and resolving role in inflammation (Bennett & Gilroy, ; Endo et al, ; Onodera et al, ). In the inflamed udder, n‐3 PUFAs may be exhausted to produce these mediators.…”
Section: Discussionmentioning
confidence: 99%
“…number of milk samples which contained target PUFA in each group (center column) and relative concentration of each PUFA substrate in subclinical and clinical mastitic milk compared with that in healthy milk (right column). EPA and DHA are the essential fatty acid for mammalians and their metabolites are reported to have anti-inflammatory and resolving role in inflammation(Bennett & Gilroy, 2016;Endo et al, 2014;Onodera et al, 2017). Abbreviations: AA, arachidonic acid; C, clinical mastitis; DHA, docosahexaenoic acid; EPA, eicosapentaenoic acid; H, healthy, OEA, oleylethanolamide; PEA, palmitoylethanolamide; PUFA, polyunsaturated fatty acid; S, subclinical mastitis Nevalainen, Graham, & Scott, 2008),.…”
mentioning
confidence: 99%
“…Mice spleen were removed, homogenized and filtered through a 200-mesh screen. Mononuclear cells (MCs) in splenocytes were isolated using lymphocyte ficoll 18 . The frequency of CD4 + CD25 + Foxp3 + Treg cells in MCs was measured to assess therapeutic effect of SIT.…”
Section: Methodsmentioning
confidence: 99%